Desarrollo de la ingeniería conceptual del proceso de producción de biogás mediante los residuos orgánicos provenientes de la Plaza Distrital de Mercado Siete de Agosto (2017)
To evaluate the characteristics of the organic residues produced in Plaza Distrital de Mercado Siete de Agosto the city of Bogotá, by means of which physical and chemical conditions such as temperature, humidity, pH, retention time, total solids and addition or not of inoculum are determined which directly influence the production of biogas, also based on a bibliographic review to be able to perform the anaerobic digestion experimentally.